Biological treatment of pesticide-containing wastewater from coffee crops: selection and optimization of a biomixture and biobed design - Oviedo-Matamoros, Fernando; Pérez-Villanueva, Marta E.; Masís-Mora, Mario; Aguilar-Álvarez, Rónald; Ramírez-Morales, Didier; Méndez-Rivera, Michael; Rodríguez-Rodríguez, Carlos E. (Frontiers in Microbiology, 2024)
The biopurification systems (BPS) or biobeds are employed for the treatment of pesticide-containing wastewater of agricultural origin. The use of these devices for pesticide removal requires the proper optimization of the composition of biomixtures (BPS active matrix) according to the target pesticides applied on a specific crop and the available materials used in their elaboration. This work aims to design a biomixture for the simultaneous treatment of several pesticides applied in coffee crops, according to local practices in Costa Rica. Three biomixtures containing either coffee husk, coconut fiber or rice husk (as the lignocellulosic substrate) were applied for the removal of 12 pesticides. The profiles of pesticide elimination and the mineralization of radiolabeled chlorpyrifos (14C-chlorpyrifos) revealed that the best performance was achieved with the coconut fiber biomixture, even though similar detoxification patterns were determined in every biomixture (according to immobilization in Daphnia magna and germination tests in L. sativa). The optimization of this biomixture´s composition by means of a central composite design permitted the definition of two optimal compositions (compost:soil:coconut fiber, % v/v) that maximized pesticide removal: i. 29:7.3:63.7 and ii. 11:7.3:81.7. The validation of these optimized compositions included the use of an alternative soil from coffee farms and resulted in overall DT50 values of 7.8-9.0 d for the pesticide mixture. Considering the removal kinetics in the optimized biomixture, a 1 m3 BPS prototype was dimensioned to be eventually used in local coffee farms. This work provides relevant information for the design and implementation of BPS at on-farm conditions for the treatment of pesticide-containing wastewater of a major crop.